Applications of Artificial Intelligence and its Role in Developing Smart Content from the Point of View of Faculty Members - Al-Shammari, Najwa Mohammed (Journal of Educational and Psychological Sciences, 2023)
The study aims at bringing to light the role of the application at artificial intelligence developing smart content from the opinion of faculty teaching staff. The study allows the analytical descriptive method. The study sample consists of 327 staff members in the Kingdom of Saudi Arabia who are chosen randomly. The study material is a questionnaire of 60 items distributed over three axes. The study conclusion is that artificial intelligence has an effective positive role in developing smart content from the perspective of faculty members with a high degree of importance, as evidenced by the average score of 4.20. There is also a clear and significant importance for artificial intelligence applications in developing smart content from the perspective of faculty members, as the average score of 4.27 shows. The conclusion indicates that there are difficult that largely affect the implementing of artificial intelligence application in developing the content with a relatively high score of 3.95. The study recommends that the necessary training need. And requirements to implement the artificial intelligence in developing smart content, to set standards of how to create smart. That suits the educational tasks it is essential to adopt a plan and a strategy is regarding to developing smart content. Finally, to develop solutions to overcome the difficulties of the application of artificial intelligence in smart content
Keywords: Applications of Artificial Intelligence; smart content